Absolute configuration determination of pharmaceutical crystalline powders by MicroED via chiral salt formation. Issue 30 (16th March 2022) - Wang, Bo; Bruhn, Jessica F.; Weldeab, Asmerom; Wilson, Timothy S.; McGilvray, Philip T.; Mashore, Michael; Song, Qiong; Scapin, Giovanna; Lin, Yiqing
Abstract : One can confidently assign the absolute configuration of a chiral molecule using crystalline powders, via microcrystal electron diffraction (MicroED) analysis. Abstract : Microcrystal electron diffraction (MicroED) has established its complementary role alongside X-ray diffraction in crystal structure elucidation. Unfortunately, kinematical refinement of MicroED data lacks the differentiation power to assign the absolute structure solely based on the measured intensities. Here we report a method for absolute configuration determination via MicroED by employing salt formation with chiral counterions.